2020
DOI: 10.1186/s13690-020-00418-x
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues on ‘challenges and opportunities towards the road of universal health coverage (UHC) in Nepal: a systematic review’

Abstract: Challenges and opportunities towards the road of universal health coverage (UHC) in Nepal: a systematic review' is a policy review paper and we published in BMC-Archives of Public Health. Policy research is the process of conducting research, analysis of, a fundamental social problem in order to provide policymakers with pragmatic, action-oriented recommendations for alleviating the problem. The objective of this paper is to illustrate some methodological issues used in that paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…is finding was also revealed by other studies [22,[36][37][38]. is might be due to the accessibility of public health centers in rural areas and the good quality of services at private health facilities.…”
Section: Discussionsupporting
confidence: 72%
“…is finding was also revealed by other studies [22,[36][37][38]. is might be due to the accessibility of public health centers in rural areas and the good quality of services at private health facilities.…”
Section: Discussionsupporting
confidence: 72%
“…Nonetheless, these studies have not explored the factors that might contribute to enrollment from purchaser side. Usually, these studies are lacking a balance in both demand and supply, poor in policy and program review [36] and have drawn one sided conclusion. None of the studies clearly investigated the characteristics of dropout, multiple factors associated with enrollment and drop-out in wide array and how the program would be successful.…”
Section: Theoretical Groundingsmentioning
confidence: 99%
“…Previous reviews were conducted in Africa [ 37 ] and low- and middle-income countries (LMICs) outside Africa around UHC [ 2 , 52 , 53 ]. These previously conducted investigations focused on health financing and suggested that financial constraints are a significant limitation to accessing quality healthcare services in LMICs.…”
Section: Discussionmentioning
confidence: 99%